1997
DOI: 10.1111/j.1440-1797.1997.tb00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased release of myeloperoxidase in vitro from neutrophils of patients with myeloperoxidase‐specific anti‐neutrophil cytoplasmic antibody (MPO‐ANCA) related glomerulonephritis

Abstract: Summary: In order to elucidate the role of neutrophils in the pathogenesis of MPO‐specific anti‐neutrophil cytoplasmic antibody (MPO‐ANCA) related glomerulonephritis (GN), MPO release, beta‐glucuronidase (BGL) release, superoxide anion (O2−) production from the neutrophils of patients with MPO‐ANCA related GN were measured. the effect of plasma on MPO release from neutrophils was also studied in patients with MPO‐ANCA related GN. Neutrophils and plasma were obtained from patients with MPO‐ANCA related GN, GN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…It was demonstrated in vitro that the neutrophils, the majority of MPO + cells, in patients with ANCA‐associated vasculitis are activated by MPO‐ANCA and interleukin‐8, thus, inducing them to adhere to the endothelium 7 . With regard to the MPO‐ANCA‐positive endothelium, it was demonstrated that neutrophils in the active phase of MPO‐ANCA‐associated nephritis are apt to release MPO, and that positively‐charged MPO can easily bind to the negatively‐charged endothelium of the glomeruli 8 . Furthermore, the chromatin fibers, so called neutrophil extracellular traps, may be released by ANCA‐stimulated neutrophils that contain MPO 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated in vitro that the neutrophils, the majority of MPO + cells, in patients with ANCA‐associated vasculitis are activated by MPO‐ANCA and interleukin‐8, thus, inducing them to adhere to the endothelium 7 . With regard to the MPO‐ANCA‐positive endothelium, it was demonstrated that neutrophils in the active phase of MPO‐ANCA‐associated nephritis are apt to release MPO, and that positively‐charged MPO can easily bind to the negatively‐charged endothelium of the glomeruli 8 . Furthermore, the chromatin fibers, so called neutrophil extracellular traps, may be released by ANCA‐stimulated neutrophils that contain MPO 9 …”
Section: Discussionmentioning
confidence: 99%
“…7 With regard to the MPO-ANCA-positive endothelium, it was demonstrated that neutrophils in the active phase of MPO-ANCA-associated nephritis are apt to release MPO, and that positively-charged MPO can easily bind to the negatively-charged endothelium of the glomeruli. 8 Furthermore, the chromatin fibers, so called neutrophil extracellular traps, may be released by ANCA-stimulated neutrophils that contain MPO. 9 Double staining for MPO and endothelial cell markers in the present study indicated that MPO immunopositivity was frequently identified in CD31 + , CD34 + , or factor 8 + endothelial cells, while MPO immunopositivity was identified in some CD34endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the normal formation of azurophil granules, in which MPO is enclosed, BGL release and O 2 À production were assayed. BGL release was elicited by methods described previously (Minoshima et al, 1997). The patient, patient's mother and healthy control showed no difference in BGL and O 2 À production.…”
Section: Neutrophil Functions and Mpo Activitymentioning
confidence: 99%
“…Beta-glucuronidase activity and release was elicited by methods described previously (Minoshima et al, 1997). Cell supernatant and homogenate (40 Al) was treated with 1 mmol/l 4-methylumbelliferyl-beta-D-glucuronide, 0.05% Triton X-100 and 0.1 mol/l sodium acetate buffer (pH 3.5) in 96-well flat bottom plate.…”
Section: Measurement Of Beta-glucuronidase (Bgl) Activitymentioning
confidence: 99%
“…Furthermore, histological documentation of brain in this disease is extremely rare. On the other hand, the etiology of the capillaritis has been postulated to be the release of enzymes including MPO from neutrophils, which are activated by ANCA and cytokines, also known as the ANCA-cytokine sequence theory [4,5]. However, immunohistochemical detection of MPO-positive cells on the capillary has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%